Analysis of Physical and Technical Training Strategies for Enhancing Pencak Silat Athletes Performance: A Literature Review - Angger Widorotama; Andi Nova; Yudhi Teguh Pambudi; Muhammad Maulana Fajar; Novriansyah Novriansyah; Eko Putra Utama (Universitas Negeri Semarang, 2026)
The rapid development of Pencak Silat into an international competitive sport demands flawless physical and technical readiness from athletes. Physical fatigue in the third round is often the primary cause of a 20–30% decrease in technical accuracy and significantly increases the risk of musculoskeletal injuries. Although the importance of physical conditioning is widely recognized, a comprehensive synthesis evaluating modern sports science training methods remains limited. Therefore, this study aims to map empirically tested physical conditioning methods to serve as a scientific reference for designing effective training programs for Pencak Silat athletes. This study utilized a qualitative descriptive literature review design. The data analysis technique involved an annotated bibliography approach to interpret and compare findings from original research articles published between 2020 and 2025. The literature review reveals that jump rope training effectively enhances straight kick skills in athletes. For crescent kicks (tendangan sabit), both plyometric and circuit training significantly improve performance; however, circuit training yields a substantially higher increase in kick speed (62.06%) compared to standalone plyometric training (36.56%). To address physical degradation, hollow sprint and shadow fight exercises demonstrate equal effectiveness in boosting VO2max capacity , while circuit training effectively enhances general endurance. Furthermore, integrating physical and technical training offers a dual benefit, improving kick speed while increasing anaerobic endurance by 21%. In conclusion, the application of sports science-based training methods is empirically proven to be far more effective and efficient than conventional methods. An integrative strategy combining physical and technical training is highly recommended during the pre-competition phase to achieve peak physical condition alongside sharper technical execution.